Analisa dan Perbaikan Kerusakan Cutter Mesin Milling F4.04 - Asep apriana (Politeknik Negeri Jakarta, 2023)
Failure studies on the F4.04 milling machine cutter that frequently occur in the manufacturing industry have been conducted using applied failure analysis and repair methods. This study aims to analyze the damage to the F4.04 milling machine cutter and carry out repairs according to existing standards. The analysis of the root causes of damage and appropriate repairs is expected to enhance efficiency, productivity, and reduce production costs in the manufacturing industry. This analysis describes the results of visual observations of damage to the cutter in the form of fractures at the edges and surface wear. Fractures at the cutter edges appear irregularly, caused by excessive cutting loads. Excessive cutting loads result from improper feed speeds and excessive cutting depths. Process instability also contributes to cutter damage. Excessive vibration in the milling machine generates impacts or collisions that damage the cutter and accelerate wear. Excessive cutting loads and cutting instability are initiated by damage to bearing components and the use of non-standard V-belt sizes. This study provides a better understanding of the types of cutter damage and influencing factors, which can be utilized to enhance cutting efficiency and cutter lifespan. It is expected that this study will contribute to identifying the exact causes of damage and designing appropriate repairs, thereby improving production quality, and reducing the risk of damage to F4.04 milling machines in the future.